X-ray pulsar GRO J1008-57 as an orthogonal rotator - Tsygankov Sergey S.; Doroshenko Victor; Mushtukov Alexander A.; Poutanen Juri; Di Marco Alessandro; Heyl Jeremy; La Monaca Fabio; Forsblom Sofia V.; Malacaria Christian; Marshall Herman L.; Suleimanov Valery F.; Svoboda Jiri; et al. (EDP SCIENCES S A, 2025)
X-ray polarimetry is a unique way to probe the geometrical configuration of highly magnetized accreting neutron stars (X-ray pulsars). GRO J1008-57 is the first transient X-ray pulsar observed at two different flux levels by the Imaging X-ray Polarimetry Explorer (IXPE) during its outburst in November 2022. We find the polarization properties of GRO J1008-57 to be independent of its luminosity, with the polarization degree varying between nondetection and about 15% over the pulse phase. Fitting the phase-resolved spectro-polarimetric data with the rotating vector model allowed us to estimate the pulsar inclination (130 & DEG;, which is in good agreement with the orbital inclination), the position angle (75 & DEG;) of the pulsar spin axis, and the magnetic obliquity (& SIM;74 & DEG;). This makes GRO J1008-57 the first confidently identified nearly orthogonal rotator among X-ray pulsars. We discuss our results in the context of the neutron star atmosphere models and theories of the axis alignment of accreting pulsars.